Gut microbiome modulation during treatment of mucositis with the dairy bacterium Lactococcus lactis and recombinant strain secreting human antimicrobial PAP. Issue 1 (December 2018) - Carvalho, Rodrigo; Vaz, Aline; Pereira, Felipe; Dorella, Fernanda; Aguiar, Eric; Chatel, Jean-Marc; Bermudez, Luis; Langella, Philippe; Fernandes, Gabriel; Figueiredo, Henrique; Goes-Neto, Aristóteles; Azevedo, Vasco
Abstract Mucositis is an inflammatory condition of the gut, caused by an adverse effect of chemotherapy drugs, such as 5-fluorouracil (5-FU). In an attempt to develop alternative treatments for the disease, several research groups have proposed the use of probiotics, in particular, Lactic Acid Bacteria (LAB). In this context, the use of recombinant LAB, for delivering anti-inflammatory compounds has also been explored. In previous work, we demonstrated that eitherLactococcus lactis NZ9000 or a recombinant strain expressing an antimicrobial peptide involved in human gut homeostasis, the Pancreatitis-associated Protein (PAP), could ameliorate 5-FU-induced mucositis in mice. However, the impact of these strains on the gut microbiota still needs to be elucidated. Therefore, in the present study, we aimed to characterize the effects of bothLactococci strains in the gut microbiome of mice through a 16 S rRNA gene sequencing metagenomic approach. Our data show 5-FU caused a significant decrease in protective bacteria and increase of several bacteria associated with pro-inflammatory traits. TheLactococci strains were shown to reduce several potential opportunistic microbes, while PAP delivery was able to suppress the growth ofEnterobacteriaceae during inflammation. We conclude the strain secreting antimicrobial PAP was more effective in the control of 5-FU-dysbiosis.